The Representation of Gender Stereotype in the Narrative Texts Provided in the ELT Textbook for Junior High School Students - Amalia, Ainun Na'imah Putri; Ariyanto, Sugeng; Andayani, Made Adi (EFL Education Journal, 2022)
The purpose of this study is to know whether or not there is a gender stereotype representation in the narrative texts provided in the ELT textbook for junior high school students. The researcher used Haliday’s transitivity analysis and Fairclough framework as an indepth identification method of Critical Discourse Analysis (CDA). Based on the research result, there are 100 processes embedded to the male characters and 40 processes embedded to the female characters. This shows a significant gap which means that the male characters of the narrative texts are portrayed as more dominant than the female.